2013
DOI: 10.1155/2013/302325
|View full text |Cite
|
Sign up to set email alerts
|

High-Frequency Ultrasound Imaging to Evaluate Liver Fibrosis Progression in Rats and Yi Guan Jian Herbal Therapeutic Effects

Abstract: The animals used in liver fibrosis studies must usually be sacrificed. Ultrasound has been demonstrated to have the ability to diagnose hepatic fibrosis and cirrhosis in experimental small-animal models. However, few studies have used high-frequency ultrasound (HFU, 40 MHz) to monitor changes in the rat liver and other hollow organs longitudinally. In this study, liver fibrosis was induced by administering dimethylnitrosamine (DMN) in SD rats, aged 8 weeks, for three consecutive days per week for up to 4 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 36 publications
0
10
0
1
Order By: Relevance
“…After anesthesia, the abdominal area was shaved and cleaned. Ultrasound exams were performed using L40‐8/12, linear transducer of 20 MHz lLongitudinal evaluation of each rat's abdomen was blindly scanned on day 0, 7, 14, and 21, and portal vein caliber (in mm) was determined …”
Section: Methodsmentioning
confidence: 99%
“…After anesthesia, the abdominal area was shaved and cleaned. Ultrasound exams were performed using L40‐8/12, linear transducer of 20 MHz lLongitudinal evaluation of each rat's abdomen was blindly scanned on day 0, 7, 14, and 21, and portal vein caliber (in mm) was determined …”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, the qualitative scoring system applied allowed to find significant differences between the different types of infections. It should be considered that both the quantitative and qualitative applied in our study have been extrapolated from numerous pre-clinical and clinical reports (Aubé et al, 1999; Mathiesen et al, 2002; Lu et al, 2003; Bonekamp et al, 2009; Lessa et al, 2010; Resende et al, 2011; Chen et al, 2013). Since this is the first application in a murine model of bacterial infection, the lack of significance might be more related to the need of a diversified diagnostic approach between different species than to the absence of pathologic ultrasonographic features.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, transient and real-time elastography are being used to assess more objectively and accurately tissue elasticity but they showed to be reliable only for extensive fibrosis or cirrhosis (Bonekamp et al, 2009; Gerstenmaier and Gibson, 2014; Heller and Tublin, 2014). Most pre-clinical studies focused on steato-fibrosis have used cirrhosis models induced with different chemicals and/or bile duct ligation, or with genetically engineered (Lee et al, 2005; Guimond et al, 2007; Yan et al, 2007; Lessa et al, 2010; Hayashi and Sakai, 2011; Chen et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Yi Guan Jian (YGJ) is a traditional Chinese formula used to treat diseases induced by reduced liver health, and previous studies have demonstrated that YGJ may reverse liver cirrhosis ( 7 , 8 ). However, the effect of YGJ on BM-MSCs remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%